2015
DOI: 10.3892/ol.2015.3310
|View full text |Cite
|
Sign up to set email alerts
|

Anti-metastatic effect of jolkinolide B and the mechanism of activity in breast cancer MDA-MB-231 cells

Abstract: Abstract. Tumor metastasis is the main cause of mortality in cancer patients. However, no effective therapies are currently available to prevent metastasis. Cell adhesion to the extracellular matrix (ECM) is crucial in cancer progression and metastasis. Thus, suppression of cell adhesion may be an effective therapeutic strategy for the prevention of metastasis. In the present study, the anti-adhesion and anti-invasion effects of jolkinolide B, a diterpenoid compound from Euphorbia fischeriana Steud, that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…It has been reported that JB regulates proliferation and induces apoptosis in human leukemic U937 cell7. Another document evaluates the anti-metastatic role and mechanisms of JB on breast cancer MDA-MB-231 cells by the integrin/FAK and ERK pathways in vitro 8.…”
mentioning
confidence: 99%
“…It has been reported that JB regulates proliferation and induces apoptosis in human leukemic U937 cell7. Another document evaluates the anti-metastatic role and mechanisms of JB on breast cancer MDA-MB-231 cells by the integrin/FAK and ERK pathways in vitro 8.…”
mentioning
confidence: 99%
“…In past decades, many natural products including berberine [ 21 ], resveratrol [ 22 ] and quercetin [ 23 ] were found to exhibit significant anti-cancer effects and thus were applied in clinic. Jolkinolide B, a diterpenoid compound isolated from the dried plant roots of Euphorbia Fscheriana Steud, has previously been reported to have anticancer effects on cancer, such as inhibiting the proliferation of mouse melanoma [ 13 ], inducing the apoptosis of breast cancer [ 24 , 25 ] and prostate cancer [ 26 ], and suppressing the metastatic activity of breast cancer cells [ 10 ]. As determined here, the IC50 of JB against CRC (18.25–38 µM, 48 h) is comparable to or smaller than those well-known promising agents including resveratrol (164.7 μM, 48 h) [ 27 ], quercetin (81.65 ± 0.49 μM, 48 h) [ 28 ] or some first line chemotherapy (5-FU, 92.85 µM, 72 h) [ 29 ], we speculate that JB could be a potential anticancer agent for CRC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Jolkinolide B (JB) is a bioactive diterpenoid component isolated from the dried roots of Euphorbia fischeriana Steud. It has been reported that JB exhibited anti-adhesion and anti-invasion effects in human breast cancer MDA-MB-231 cells through the suppression of β1-integrin expression and the phosphorylation of focal adhesion kinase (FAK) [ 10 ]. Moreover, JB can induce apoptosis in human chronic myeloid leukemia [ 11 , 12 ] via decreasing PI3K/Akt and the inhibitor of apoptosis protein (IAP) family proteins, and activating caspase-3 and -9.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately many plant-derived compounds have been discovered to effectively suppress metastasis of tumor cells [ 47 , 48 , 49 ]. Compound 1 was found to inhibit the attachment of MDA-MB-231 cells to fibronectin, with these effects being mediated by the integrin/FAK and ERK pathways [ 50 ]. Compound 8 has been demonstrated to inhibit VEGF-induced angiogenesis by targeting the VEGFR-2 signaling pathway [ 51 ].…”
Section: The Anti-cancer Mechanism Of Diterpenoidsmentioning
confidence: 99%